Transabdominal laparoscopic retroperitoneal neurectomy for chronic pain after inguinal hernia repair and appendicectomy: a matched-pair study - Karampinis, Ioannis; Pilz, Lothar R.; Post, Stefan; Herrle, Florian (BMC surgery, 2017)
Chronic debilitating pain is a rare but significant cause of postoperative morbidity after inguinal surgery. Such pain is usually of neuropathic origin and frequently caused by intraoperative nerve damage. In this retrospective matched-pair study we analysed results of a minimal-invasive approach to neurectomy on quality of life and pain relief.
Gesehen am 19.10.2017